Penciptaan Karya Tari Menggunakan Model Pembelajaran Kooperatif Di Sanggar Gardancestory Bandarlampung - aryusma suhada; Susi Wenhdaningsih; Hasyimkan hasyimkan; Riyan Hidayatullah (Jurnal Seni dan Pembelajaran, 2018)
The study aimed to describe the use of cooperative learning model in the creation of dance work at Gardancestory Studio Bandarlampung. The formulation of the problem is, how the steps of model cooperative learning in the creation of works of dance. The use of cooperative learning begins with the delivery of learning objectives, the delivery of materials in the form of the basic motion of dance tradition Lampung, learners do exploration and improvisation of motion materials, learners teach the movement of exploration results to all colleagues, then learners enter into the formation stage of the series of motion, the composition of dance, the union with the accompaniment of music, and make improvements of motion and wirasa techniques in the work of dance that has been formed, the last is the evaluation between teachers and learners. Learning the creation of dance works using this cooperative model belongs to the good category, where learners experience improvement in results from all aspects of the first meeting to the seventh meeting.Penelitian bertujuan untuk mendeskripsikan penggunaan model pembelajaraan kooperatif dalam penciptaan karya tari di sanggar Gardancestory Bandarlampung. Rumusan masalahnya yakni, bagaimanakah langkah-langkah model pembelajaraan kooperatif dalam penciptaan karya tari. Penggunaan pembelajaran kooperatif dimulai dari penyampaian tujuan pembelajaran, penyampaian materi berupa ragam gerak dasar tari tradisi Lampung, peserta didik melakukan tahap eksplorasi dan improvisasi materi gerak, peserta didik mengajarkan gerak hasil eksplorasi kepada seluruh rekannya, selanjutnya peserta didik masuk kedalam tahap pembentukan rangkaian gerak, membentuk komposisi tari, penyatuan dengan iringan musik, serta melakukan pembenahan teknik gerak dan wirasa dalam karya tari yang telah terbentuk, yang terakhir yaitu melakukan evaluasi antara pengajar dan peserta didik. Pembelajaran penciptaan karya tari menggunakan model kooperatif ini termasuk ke dalam kategori baik, dimana peserta didik mengalami peningkatan hasil diseluruh aspek dari pertemuan pertama hingga pertemuan ketujuh.Kata Kunci: Kooperatif, Penciptaan, Tari.